2021
DOI: 10.1371/journal.pntd.0009541
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia species in human infections in Mexico: Identification of B. cepacia, B. contaminans, B. multivorans, B. vietnamiensis,B. pseudomallei and a new Burkholderia species

Abstract: Background Burkholderia sensu stricto is comprised mainly of opportunistic pathogens. This group is widely distributed in the environment but is especially important in clinical settings. In Mexico, few species have been correctly identified among patients, most often B. cepacia is described. Methodology/Principal findings In this study, approximately 90 strains identified as B. cepacia with the VITEK2 system were isolated from two medical centers in Mexico City and analyzed by MLSA, BOX-PCR and genome analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…known as Pseudomonas cepacia could cause decay of onion bulbs in 1950. Subsequently, several studies have reported this bacterium as an opportunistic human bacterial pathogen (Martina et al, 2018;Radilla et al, 2021). However, in agriculture, B. cepacia has multiple functions such as biological control, biodegradation, and promoting plant growth, showing its broader agricultural application pros-Cauduro been developed correspondingly with the advancements in molecular biology techniques.…”
Section: Discussionmentioning
confidence: 99%
“…known as Pseudomonas cepacia could cause decay of onion bulbs in 1950. Subsequently, several studies have reported this bacterium as an opportunistic human bacterial pathogen (Martina et al, 2018;Radilla et al, 2021). However, in agriculture, B. cepacia has multiple functions such as biological control, biodegradation, and promoting plant growth, showing its broader agricultural application pros-Cauduro been developed correspondingly with the advancements in molecular biology techniques.…”
Section: Discussionmentioning
confidence: 99%